Uwagi krytyczne do projektu ustawy o ochronie praw nabywcy lokalu mieszkalnego lub domu jednorodzinnego oraz o Deweloperskim Funduszu Gwarancyjnym - Szulc, Piotr (Studia Prawa Publicznego, 2021)
The article presents reflections on the bill on the protection of the rights of a purchaser of residential premises or a single-family house and on the Developer Guarantee Fund, Parliamentary printed matter no. 985. According to the bill drafter, the proposed changes are a response to “bankruptcies of property developer businesses and related financial losses of those who have purchased residential premises or houses through these businesses”. A number of provisions of the Act, the structure of which remains unclear, give rise to numerous interpretation disputes and significantly undermine the certainty of legal dealings. Firstly, there is no regulation regarding the supervision of the developer guarantee fund and its legal status. The regulation regarding the developer guarantee fund is scarce compared to that of the Bank Guarantee Fund, thus leaving significant room for abuse. Secondly, the bill is significantly defective in its lacking any method for calculating the contribution depending on the level of risk of a given developer going bankrupt. All entities are to be subject to the same contribution.